Pulmonary complications and respiratory management in neurocritical care: a narrative review. Issue 7 (5th April 2022) - Wen, Junxian; Chen, Jia; Chang, Jianbo; Wei, Junji
Abstract : Abstract: Neurocritical care (NCC) is not only generally guided by principles of general intensive care, but also directed by specific goals and methods. This review summarizes the common pulmonary diseases and pathophysiology affecting NCC patients and the progress made in strategies of respiratory support in NCC. This review highlights the possible interactions and pathways that have been revealed between neurological injuries and respiratory diseases, including the catecholamine pathway, systemic inflammatory reactions, adrenergic hypersensitivity, and dopaminergic signaling. Pulmonary complications of neurocritical patients include pneumonia, neurological pulmonary edema, and respiratory distress. Specific aspects of respiratory management include prioritizing the protection of the brain, and the goal of respiratory management is to avoid inappropriate blood gas composition levels and intracranial hypertension. Compared with the traditional mode of protective mechanical ventilation with low tidal volume (Vt ), high positive end-expiratory pressure (PEEP), and recruitment maneuvers, low PEEP might yield a potential benefit in closing and protecting the lung tissue. Multimodal neuromonitoring can ensure the safety of respiratory maneuvers in clinical and scientific practice. Future studies are required to develop guidelines for respiratory management in NCC.